Positioning of a Volar Locking Plate with a Central Flexor Pollicis Longus Tendon Notch in Distal Radius Fractures - Kaiser, Peter; Gruber, Hannes; Loth, Fanny; Schmidle, Gernot; Arora, Rohit; Gabl, Markus (Journal of Wrist Surgery, 2019)
Background Volar locking plates with a central notch were designed to reduce the risk of flexor pollicis longus (FPL) tendon irritation after volar plating for distal radius fractures.Objective The purpose of this study was to evaluate the course of the FPL tendon after FPL-plate osteosynthesis to identify a plate position that avoids an impingement with the FPL tendon.Patients and Methods Nineteen patients treated with volar plating using an FPL plate for a distal radius fracture were evaluated. Transverse ultrasound images were used to assess whether the profile of the FPL tendon lied within the plate notch. The position of the FPL tendon on transverse ultrasound images was transferred onto postoperative dorsovolar X-ray images to define an FPL tendon corridor for a plate position not interfering with the FPL tendon.Results The FPL tendon was aligned inside the plate notch completely in three cases, partially in 11 cases, and missed the notch in five cases. An FPL corridor was defined at the level of the watershed line with all FPL tendons being completely (74%) or partially (26%) aligned inside that corridor. There was a moderate correlation between the plate notch being positioned inside this corridor and the FPL tendon being positioned inside the plate notch (r = 0.49; p = 0.033).Conclusion It seems advantageous to place the plate notch within a corridor parallel to the radial shaft between the ulnar edge of the scaphoid tubercle and the scapholunate interval for the FPL tendon protection.Level of Evidence This is Level IV study.
Keywords: flexor pollicis longus; distal radius fracture; tendon rupture; Soong classification; ultrasound